2010
DOI: 10.1080/03630242.2010.506149
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Perception of Quality of Life Among Israeli Women with and without Physical Disability

Abstract: This study compared the relationship between self-esteem and perceived quality of life among Jewish Israeli women with and without physical disabilities, and estimated the moderating effects of marital status and age on these relationships. A quasi-experimental design was employed. A total of 134 women aged from 21 to 45 years participated in the study: 70 of them with disabilities and 64 without disabilities (case and control groups, respectively). Significant differences were found between these groups in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
2
17
0
3
Order By: Relevance
“…For disabled women, SRHS was about 4-5 points higher with each year increase in age, which seems counter intuitive. Research had indicated that individuals may use social comparisons as they think about their health, that is, comparing themselves to others in their age group, those with similar chronic conditions, or those with similar socioeconomic status (Arigo, Suls, and Smyth 2012;Duvdevany 2010;Idler and Benyamini 1997;Kaplan and Baron-Epel 2003;Wolff et al 2010). The slight increase in perceptions of SRHS as the disabled women aged may have been because over time, women were able to make adjustments in management of their health conditions with improved access to regular care and services, and hence, socially compare better on their health status with other low-income disabled women without access to care.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For disabled women, SRHS was about 4-5 points higher with each year increase in age, which seems counter intuitive. Research had indicated that individuals may use social comparisons as they think about their health, that is, comparing themselves to others in their age group, those with similar chronic conditions, or those with similar socioeconomic status (Arigo, Suls, and Smyth 2012;Duvdevany 2010;Idler and Benyamini 1997;Kaplan and Baron-Epel 2003;Wolff et al 2010). The slight increase in perceptions of SRHS as the disabled women aged may have been because over time, women were able to make adjustments in management of their health conditions with improved access to regular care and services, and hence, socially compare better on their health status with other low-income disabled women without access to care.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to those without disabilities, people with disabilities had unmet health needs and experienced difficulties or disparities in obtaining health care (CDC 2011). Those with disabilities also had lower self-esteem and perceived quality of life (Duvdevany 2010), had a greater frequency of health conditions/problems (Freid, Bernstein, and Bush 2012), and reported lower SRHS than those without disabilities (Barry, Kaiser, and Atwood 2007;Bowling and Windsor 1997;Pettit et al 2001). Freid and colleagues (2012) found that the burden of chronic medical conditions has been increasing in U.S. adult women: 21 percent had two or more of nine selected chronic conditions in 2009-2010 (including hypertension, heart disease, diabetes, cancer, stroke, chronic bronchitis, emphysema, current asthma, and kidney disease).…”
Section: Introductionmentioning
confidence: 95%
“…; Hughes et al . ; Duvdevany ), putting them at greater risk for impaired social functioning and lower quality of life (Rosenbaum et al . ; Varni et al .…”
Section: Introductionmentioning
confidence: 99%
“…Health outcomes for youth and young adults with CP and other disabilities are often related to one's self-esteem and quality of life (Young et al 1997). For example, women with disabilities have lower levels of self-esteem when compared with women without disabilities and to men with disabilities (Nosek et al 2003;Hughes et al 2005;Duvdevany 2010), putting them at greater risk for impaired social functioning and lower quality of life (Rosenbaum et al 2007;Varni et al 2007;Russo et al 2008). Because females with CP are more vulnerable for poor outcomes it is important to explore their life experiences to identify factors improving outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of prejudices impacting the individual's desire to participate in society has been discussed by Duvdevany (2010). In her study of self-esteem and quality of life among Israeli women with and without disabilities, Duvdevany explained that prior research indicates that it is not the disability itself that negatively impacts an individual's participation in society, but rather the contextual and social barriers.…”
Section: Why Study Persons With Disabilitiesmentioning
confidence: 99%